Functional outcomes by age after inpatient stroke rehabilitation in Saudi Arabia - Bindawas SM (Dove Medical Press, 2017)
Saad M Bindawas,1 Vishal Vennu,1 Hussam Mawajdeh,2 Hisham Alhaidary2 1Department of Rehabilitation Sciences, King Saud University, Riyadh, 2Comprehensive Rehabilitation Care Department, Rehabilitation Hospital, King Fahad Medical City, Riyadh, Saudi Arabia Background: Among various risk factors, age has been identified as a nonmodifiable risk factor for stroke that influences functional outcomes after inpatient stroke rehabilitation in the developed world as well as in Saudi Arabia (SA). The demand for inpatient stroke rehabilitation services increases with population aging and stroke incidence; however, these services are limited in SA.Objective: To examine functional outcomes by age after inpatient stroke rehabilitation in SA.Patients and methods: Data from 418 patients with stroke who underwent inpatient stroke rehabilitation at the King Fahad Medical City-Rehabilitation Hospital, Riyadh, SA, between November 2008 and December 2014 were collected from electronic medical records. According to the patients’ age, we classified participants into two groups: adults, aged <65 years (n=255), and older adults, aged ≥65 years (n=163). All patients’ functional statuses at admission and discharge from inpatient stroke rehabilitation were assessed using the functional independence measure (FIM) scale.Results: The mean age was 59.9 years (SD =9.4). Older adults had significantly smaller changes in functional outcome from admission to discharge on both the total FIM (23 [SD =15.9]) and the motor FIM (21 [SD =15.4]), and they were significantly less independent (36%) compared to adults. In the adjusted models, older adults had significantly lower scores than adults, by 11 points (p<0.0001) for the total FIM score and by 10 points (p<0.0001) for the motor FIM subscale score. There was no significant change with age in the cognitive FIM subscale score.Conclusion: After inpatient stroke rehabilitation, older adults had limited functional outcomes or were less independent than adults. However, the clinical relevance of this finding is questionable, so there is currently no justification to deny patients access to intensive stroke rehabilitation solely because of advanced age. Future large-scale research is needed to confirm rehabilitation outcomes by including confounders such as social support, socioeconomics, comorbidities, and the patient’s opinion after rehabilitation. Keywords: adult, older adult, FIM